Whole Transcriptome Sequencing Analysis of the Synergistic Antimicrobial Effect of Metal Oxide Nanoparticles and Ajoene on Campylobacter jejuni - Xue, Rui; Feng, Jinsong; Ma, Lina; Liu, Chunrong; Xian, Ming; Konkel, Michael E.; Wang, Shuo; Lu, Xiaonan (Frontiers in Microbiology, 2018)
Two metal oxide (i.e., Al2O3 and TiO2) nanoparticles and ajoene, a garlic-derived organosulfur compound, were identified to be effective antimicrobials against Campylobacter jejuni, a leading cause of human gastrointestinal diseases worldwide. A significant synergistic antimicrobial effect was observed using ajoene and Al2O3/TiO2 nanoparticles in a combined manner to cause at least 8 Log10 CFU/mL reduction of C. jejuni cells. Whole transcriptome sequencing (RNA-seq) and confocal micro-Raman spectroscopic analyses revealed the antimicrobial mechanism and identified the roles of ajoene and metal oxide nanoparticles in the synergistic treatment. Ajoene and metal oxide nanoparticles mediated a two-phase antimicrobial mechanism. Ajoene served as the inducing factor at the first phase that caused injury of cell membranes and increased the susceptibility of C. jejuni to stress. Metal oxide nanoparticles served as the active factor at the second phase that targeted sensitive cells and physically disrupted cell structure. This synergistic antimicrobial treatment demonstrates a potential to reduce the prevalence of C. jejuni and other pathogens on food contact surfaces and in the food chain.